The Effect of The Cognitive Contradiction Strategy on Correcting Spelling Mistakes Among Second-Year Middle School Students (Journal of the College of Basic Education, 2026)
The current research aims to identify the role of star-shine in spelling correction among second-grade students. A quasi-experimental research method was used. The researcher, Qasdi, selected Ashur Intermediate School for Boys, affiliated with the General Directorate of Education in Baghdad, Rusafa 1. The research sample consisted of (60) students, with (30) students in the experimental group and (30) students in the control group. The research explored two possible outcomes (Chronological age calculated in months, the educational attainment of the parents, and the students’ grades for the previous academic year), and the researcher tried to control a number of variables by previous studies and literature that may affect this type. After the researcher identified the scientific material for the dictation material in the Arabic language book prescribed for teaching second-grade intermediate students for the academic year (2024-2025) in Iraq, The researcher prepared a final test as a tool for his research after verifying its validity and reliability. He applied it to the experimental and control research groups at the end of the experiment. Using the t-test for two independent samples, the study resulted in the following result: There is a students who studied the spelling material the cognitive contradiction strategy and the average traditional way, in favor of the experimental group at the (005) level. In light of the result and its interpretation, the researcher made a number of conclusions, recommendations, and suggestions that support the educational process.